Pengaruh Brand Trust dan Online Customer Review Terhadap Minat Beli Pada Marketplace Bukalapak - Anindya, Auryn Latifa; Akbar, Ridho Riadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this research is to understand how brand trust and online customer reviews affect buying interest in the Bukalapak marketplace. This research uses quantitative methods with descriptive and verification approaches, using a combination of primary and secondary data. The researcher involved 100 respondents, who were selected using the Slovin formula from the total population of active marketplace users in 2024, namely 65 million users. This research confirms that aspects such as brand trust and online customer reviews have a major influence on buying interest in the Bukalapak marketplace. Based on the data, brand trust shows a significant influence on interest buying, with a tcount value of 2.166 and a significance level of 0.03. Meanwhile, online customer reviews also have a significant effect on purchase intention, as indicated by a tcount value of 6.556 with a significance level of 0.00. Together, these two factors make an important contribution to purchase intention, as evidenced by the fcount value of 31.811 and a highly significant p-value of 0.000.